THE ROLE OF TEACHERS IN INTEGRATING ENGLISH IN KINDERGARTEN DAILY ACTIVITIES - Purwanti, Elly (Madiha Press, 2024)
This study explores the vital role of teachers in integrating English language learning into daily activities in kindergarten classrooms. By incorporating English into various activities such as playtime, circle time, and storytime, teachers can create a rich language-learning environment for young learners. The findings of this study suggest that teachers play a crucial role in fostering language development and creating a positive learning experience for kindergarten students. Teachers who actively engage students in English during daily activities help to build a strong foundation for language acquisition. Through interactive games, songs, and simple conversations, teachers can make learning English fun and engaging for young children. By immersing students in the language throughout the day, teachers can ensure that students are exposed to English in a natural and meaningful way, leading to greater language proficiency over time. Overall, the study highlights the importance of teachers in shaping the language learning experience for kindergarten students and emphasizes the impact of their role in creating a supportive and enriching learning environment.